Social Behaviors, Enforcement, and Tax Compliance Dynamics - Davis, Jon S.; Hecht, Gary; Perkins, Jon D. (The Accounting Review, 2003)
We analyze the effect of social norms and enforcement on the dynamics of taxpayer compliance. Specifically, we develop two models to evaluate the movement between classes of compliant and noncompliant taxpayers. Our analysis suggests that the effect on compliance of changing enforcement levels depends on whether the taxpayer population is initially compliant or noncompliant. Compliant populations are insensitive to changes in enforcement policies until enforcement becomes sufficiently lax, when we observe a sudden shift to high levels of noncompliance in equilibrium. In contrast, relatively noncompliant populations respond to increased enforcement by gradually increasing compliance. Then, when enforcement becomes sufficiently harsh, we find a sudden shift in equilibrium to very high levels of compliance. After the taxpayer population shifts from compliance to noncompliance, or vice versa, our models predict that returning to the previous enforcement policy will not cause the population to return to its previous state. On the whole, our models' results help explain why taxpayer compliance varies across time and across geographic regions, even under similar enforcement regimes.